The Archtecture Of Holy Thresholds And Functionl Indicators For Its Development - Hasan Aziz , Abdualjawad; Muhammed Hussein Mahdi, Ali (Journal of Planner and Development, 2020)
Obiovisly that the holy thresholds are directly related to Islam and Muslims and related to the general culture of the Islamic peoples. In terms of architecture, it is considered a distinctive architectural scene that reviews the history of this origin and its architectural styles. Recently, with the increase in the number of pilgrims and visitors to the holy shrines, there is a need to develop and expand the buildings and provide them with services and introduce modern technology. The building of the holy thresholds consists of a number of functional design indicators: The general problem of research is that there is no clear theoretical framework for the design indicators for the development of the holy shrines according to the function it provides and the need to develop them. In order to find a solution to these problems, the research will deal with two axes, the first one will review the concept of architectural development and its types, and reach the identification of development indicators for archaeological historical buildings with distinctive spiritual and symbolic values. The second axis deals with the study and analysis of examples of the architecture of the existing holy shrines (Haram al-Makki and Haram Imam Redha) by reviewing The process of its creation and development throughout history to determine its functional design indicators and then reviewing the development projects. The research adopts descriptive methods for the selected samples, which include the projects of thresholds, tombs and holy sites (Haram al-Makki and Haram Imam Redha).